Sosialisasi Pengenalan dan Cara Mengembangkan Knowledge Management System (KMS) pada Institusi Pendidikan - Intan Purnamasari; Siska Siska (LPPM UNIVERSITAS DIAN NUSWANTORO, 2023)
A knowledge base is one component that is needed in any field and institution. As is known, especially in the field of education, several educational institutions, both private and state, have different rules and academic systems. One of them is an academic information system that can be applied to elementary schools. Basically, every educational institution must have an academic information system, but sometimes what is the manufacturing process or system flow like? Many educational institutions still use Ms.Office, especially Ms.Excel, in processing the results of academic activities that have been carried out and are still limited to grade processing. This socialization is more about introducing how an educational institution can develop knowledge for an academic information system by utilizing the Knowledge Management System (KMS). From the results of socialization, especially in Tambaksari Village, Pedes Karawang, there are higher education institutions and other similar institutions such as schools and so on, they can develop an academic information system that has appropriate values to be more efficient. Keywords: Knowledge base, knowledge management, knowledge management system, education